Ketidakpastian Dan Risiko Yang Dialami Masyarakat Di Era Modernisasi - Martina Eka Saputri; Icha Cahya Kusuma Ningtias; Nurdiana Holida (Universitas Katolik Widya Karya Malang, 2023)
In times like today, it is certain that people in their lives will experience an event called risk. This incident is bound to happen to everyone in any way. Therefore, to minimize the negative impact due to these risks, it is necessary to have a solution on the risk side to deal with these risks. Risk is a synonym of the English-speaking Risk Society, which means that in reality in social life there must be a problem or uncertainty that is experienced. In 1986 risk could be described in a structural situation, for example, industrialization, the emergence of the modernization era, and so on. Because basically the era of modernization gave rise to many technologies that are easy to use so that they can affect existing life. According to Anthony Giddens, modernization is a culture of risk. The risk community is a meaning used because something has changed towards something new in people's lives at this time. In addition, the figure who discussed the risk community was Ulrick Beck. He stated that criticism of mathematical morality from expert thinking is that public discourse about risk making is something that can be avoided from the structural conditions of society. Then the figure who also discusses the risk community is Mary Douglas, an anthropologist who discusses cultural theory.